ANALYSIS OF USING DIGITAL LEARNING MATERIALS IN ENGINEERING LABORATORY COURSES - TSVETELINA GEORGIEVA; TZVETELIN GUEORGUIEV; SEHER KADIROVA; BORIS EVSTATIEV; NIKOLAY MIHAILOV (Journal of Engineering Studies and Research)
The paper presents an analysis of the use of digital learning materials in engineering laboratory courses. Interviews have been conducted with lecturers from several engineering faculties of the University of Ruse ‘Angel Kanchev’, such as: the Faculty of Electrical Engineering, Electronics and Automation, the Faculty of Transport, and the Faculty of Mechanical and Manufacturing Engineering. The aim of the interviews is to investigate the capacity and understanding of the lecturers in respect to using digital learning materials in laboratory courses. The obtained results demonstrate that digital learning materials are perceived as a useful tool to achieve better engagement of students in the educational processes. This would require continuous additional efforts by the teaching staff and permanent updating of their specific and digital competences.